Seafarers’ Wellbeing on Board: Scoping Review - Şenbursa, Nihan (Transactions on Maritime Science, 2024)
The author aims at synthesising the published literature on seafarers' mental and physical health and wellbeing. The reason for this study is to reveal the published literature on the mental and physical difficulties faced by seafarers, which have gained more importance in recent years. Especially during the COVID19 pandemic and afterwards, seafarers who have been on board much longer than their contracts had to go through very difficult processes. In this paper the studies that examine the concepts affecting mental health, such as depression, anxiety, isolation, psychological well-being and stress, and physical health, such as insomnia, poor alimentation, and fatigue are included. This review covers thematic analysis, results, and literature on wellbeing of the seafarers. Findings of the studies in the existing literature reveal that ship operators need to provide access to mental health resources and support services, such as counselling, to help seafarers cope with the stress and isolation of life at sea. On the other hand, opportunities for seafarers to maintain contact with their families and support their mental health need to be ensured while they are away from home. Supporting work-life balance provides opportunities for seafarers to access internet and communication facilities, offering regular shore leave, and encouraging engagement in activities that promote mental well-being. Moreover, for physical wellbeing ship management organisations should ensure access to medical care on board apart from telehealth, including emergency medical services, to address any physical health concerns. Organisational culture will promote a workplace culture that supports seafarers' mental and physical health and encourages open communication. This study provides a foundation for future maritime research and facilitates exploration of these concepts.